Role of Metastasis Suppressor KAI1/CD82 in Different Cancers - Yan, Wei (J Oncol, 2021)
Metastasis is one of the characteristics of malignant tumors and the main cause of death worldwide. The process of metastasis is mainly affected by tumor metastasis genes, tumor metastasis suppressor genes, tumor microenvironment, extracellular matrix degradation, and other factors. Thus, it is essential to elucidate the mechanism of metastasis and find the therapeutic targets in order to prevent the development of malignant tumors. KAI1/CD82, a member of tetraspanin superfamily of glycoproteins, has been reported as a tumor metastasis suppressor gene in various types of cancers without affecting the tumor formation. Many studies have demonstrated that low expression of KAI1/CD82 might lead to poor prognosis due to its interactions with other tetraspanins and integrins, resulting in the regulation of cell motility and invasion, cell-cell adhesion, and apoptosis. Considering its pathological and physiological significance, KAI1/CD82 could be a potential strategy for clinical predicting and preventing tumor progression and metastasis. The present review aims to discuss the role of KAI1/CD82 in metastasis for different cancers and examine its prospects as a metastasis biomarker and a therapeutic target.